2022
DOI: 10.1177/09544062211068643
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Piston–Cylinder Interfaces of Axial Piston Machines for Running in the High-Pressure Regime with Water as the Hydraulic Fluid

Abstract: Water’s low viscosity renders it a poor lubricant, but its green footprint, non-toxicity, inflammability, and low cost make it a desirable hydraulic fluid. Axial piston machines running on water are commercially available, but, especially the larger units, do not operate in the high-pressure regime ( ≥300 bar). The present work investigates micro surface shaping as a design solution for the critical piston–cylinder interfaces of these units, which are particularly hard-struck by the low viscosity of water in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The energy dissipation of the piston-cylinder pair is mainly composed of frictional losses and leakage losses (Fang and Shirakashi, 1995). As shown in Fig.…”
Section: Calculation Of the Energy Dissipation Characteristic Paramet...mentioning
confidence: 99%
“…The energy dissipation of the piston-cylinder pair is mainly composed of frictional losses and leakage losses (Fang and Shirakashi, 1995). As shown in Fig.…”
Section: Calculation Of the Energy Dissipation Characteristic Paramet...mentioning
confidence: 99%
“…The average speed is more than 3500 r/min, and some EHA pumps can even reach 22,500 r/min and the operating life can reach more than 20,000 h [15]. Vacca et al from Purdue University used the virtual prototype method to design the surface texture of the micro-surface contour of the pistoncylinder interface of the piston pump and studied the influence of the contour shape on the load under the high-pressure condition and concluded that the concave hole contour could best improve the overall load support under the high-pressure stroke [16]. Domestic research on the high speed of the bivariate axial piston pump is mainly carried out in colleges and universities.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, these machines operate with hydraulic oil as the working fluid. However, over the past few years, several researchers have demonstrated the use of water as the working fluid for these machines [1]- [3]. Using water as a working fluid has several advantages: it is sustainable, environmentally friendly, non-flammable, non-toxic, and acts as an effective coolant for the machine.…”
Section: Introductionmentioning
confidence: 99%